Improving the Bojonegoro Community's Economy Based on Sustainable Tourism Development - Robiatus Stia Ningrum; Septi Wulandari; Heny Suhindarno (Yayasan Riset dan Pengembangan Intelektual, 2023)
Improving the community's economy is the main goal for every region, including Bojonegoro. One approach adopted to achieve this goal is through sustainable tourism development. This research aims to analyze the impact and potential of developing sustainable tourism in improving the economy of the Bojonegoro community. The research results show that the development of sustainable tourism has great potential to improve the economy of the Bojonegoro community. Various initiatives for tourism infrastructure development, environmental conservation, and local community empowerment have had a significant positive impact. Increasing tourist visits, community involvement in the tourism industry, and income diversification are indicators of the success of implementing sustainable tourism-based development. However, this research also identified several challenges, such as conflicts of interest between environmental conservation and tourism infrastructure development. Therefore, cooperation between government, the private sector, and society is needed to create balanced and sustainable policies. In conclusion, the development of sustainable tourism can be the main driver in improving the economy of the Bojonegoro community. By paying attention to economic, social, and environmental aspects, sustainable policy implementation can create long-term positive impacts, open up new opportunities, and sustainably empower local communities.